SOSIALISASI EKSPERIMEN FENOMENA QUANTUM FLUORESENSI KEPADA SISWA SMPN 28 BENGKULU UTARA - I Nyoman Candra; Listiono, Arsela Eko; Febriansyah, Muhammad; Nabila, Anggun T.; Nurhamidah; Elvinawati (Universitas Bengkulu, 2025)
The subject of Chemistry is still relatively unfamiliar among junior high school students because it is still part of the broader Science subject taught at that level. This is also the case at SMPN 28 Bengkulu Utara, where students are still unfamiliar with chemistry. To introduce chemistry and create a positive impression of the subject among students at SMPN 28 Bengkulu Utara, an outreach activity was conducted focusing on interesting chemical phenomena — in this case, the phenomenon of quantum fluorescence.During the activity, explanations were given about the meaning of fluorescence, the causes behind it, and its applications in everyday life. The outreach activity also included demonstrations of the fluorescence phenomenon. Participants engaged in the event enthusiastically, as seen through the students' active participation. This activity is expected to help participants become more familiar with chemistry, a subject that has long been considered difficult, intimidating, and abstract. Keywords: fluorescence; chemistry; carbon quantum dots; light